Memahami Kreatifitas Iklan - Udin, Noor (Humaniora, 2010)
Ads always exist in our midst, apparently was never fail to greet, inform and persuade us. Conscious or not, advertising has become an unavoidable part our lives from when we wake up until we sleep. This paper explores how advertising works and how it is able to hold their positions in the hearts of consumers or its target audience. The important thing that must be observed in the ad is the message in it. Messages should be delivered in an as simple as possible way so that the target audience is not biased by dualities in the message. The common understanding is the measure of success that is associated with the after sale just the same as another type of capital investment. This understanding affects advertisers to create simple and rudimentary ads. The desire to enjoy and see pretty, intelligent and communicative advertisements must be born from the campus. The advertisements are not just created to represent the intent of advertisers, but also to carry moral and educational variables for the audience.